A systematic review on identifying risk factors associated with early sexual debut and coerced sex among adolescents and young people in communities. Issue 3 (23rd October 2017) - Lee, Regina Lai Tong; Yuen Loke, Alice; Hung, Tommy Tsz Man; Sobel, Howard
Abstract : Aims and objectives: To review literature on identifying the risk factors associated with early sexual coerced debut with the aim to facilitate the healthcare workers' planning of relevant health services to improve intervention strategies for delaying of early coerced sexual debut or forced sexual debut (CSD/FSD) in the communities. Background: Identifying the risk factors associated with coercion at first sex is crucial for developing appropriate sexual and reproductive health information and health promotion in response. However, current knowledge about the risk factors associated with coercion, sexual debut (SD) and delayed SD among young people is limited. Health information programmes are important during adolescence, when young people are developing their values and beliefs about sexual activity and sexual norms. However, little is known about those risk factors on initiation of early sexual debut to plan relevant interventions that can delay SD and prevent CSD/FSD in this population. Design: A systematic review. Methods: An extensive literature search using MEDLINE (PubMed), Nursing Journals (PubMed), Web of Science, PsychINFO and CINAHL. Results: The search generated 39 published studies that met our inclusion and exclusion criteria. Thirty‐two articles passed the quality appraisal and were selected. This review identified six domains of risk factors, categorised as: (1) the individual domain, (2) the family domain, (3) the partner/peer domain, (4) the school domain, (5) the community domain and (6) the cultural domain. These factors highlight the influences on sexual decision‐making among adolescents and young people and the timing of their first sexual intercourse. Conclusion: It is important to use the outcome of this review's categorisation of identified risk factors to facilitate the healthcare workers and plan relevant sexual and reproductive health programmes more accessible to adolescents, especially young females and their parents. There is a need to evaluate the impact of these programmes that can delay SD and prevent CSD/FSD in this population. Relevance to clinical practice: The results of this study could provide guidance on the planning of effective interventions for delaying of early CSD/FSD in the communities.